Cause, manner and age of death in a series of decedents with tattoos presenting for medicolegal autopsy. (May 2019) - Stephenson, Lilli; Byard, Roger W.
Abstract: Tattoos have been previously linked to high-risk behaviours involving drug use, sexual promiscuity, mental health disorders such as depression and subsequent suicidality, aberrant personality traits including lack of sociability and reduced inhibition, psychopathy and schizophrenia. All of these have been associated with violent and early deaths. Given the recent increase in numbers of individuals being tattooed in Western communities, a retrospective study was undertaken of 100 consecutive autopsy cases with tattoos over a 5-year period from 2013 to 2017, with age and sex-matched controls. Although those with ≥5 tattoo regions were slightly younger than those with <5, 47.4 compared to 49.7 years, this did not reach statistical significance (p = 0.35). Similarly, there were no significant differences in the cause and manner of death among the groups (p = 0.09). This study has, therefore, shown no significant association between the number of tattoos and premature mortality, or between the cause and manner of death and the presence or absence of tattoos. Previous stereotypes regarding tattooed individuals may no longer apply. Highlights: Tattoos have been previously linked to high-risk behaviours. No significant association was shown between the number of tattoos and premature mortality. There were also no association between the cause/manner of death and tattoos. Previous stereotypes regarding tattooed individuals may no longer apply.